2013
DOI: 10.1002/jgrc.20186
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Atlantic off‐equatorial eastward currents during 1993–2010 using a synthetic method

Abstract: [1] We have developed, validated, and applied a synthetic method to monitor the offequatorial eastward currents in the central tropical Atlantic. This method combines highdensity expendable bathythermograph (XBT) temperature data along the AX08 transect with altimetric sea level anomalies (SLAs) to estimate dynamic height fields from which the mean properties of the North Equatorial Countercurrent (NECC), the North Equatorial Undercurrent (NEUC) and the South Equatorial Undercurrent (SEUC), and their variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 114 publications
(164 reference statements)
7
32
2
Order By: Relevance
“…Hüttl‐Kabus and Böning () also found a more northward position and higher transports between April and August and a more southward position and lower transports between September and March in their model simulation. The seasonal cycle of NEUC transport estimates in TRATL01 is also consistent with the synthesis product of Goes et al (). Similar to Goes et al (), we found a semiannual cycle of the NEUC central position along 23°W, although the timing of maxima and minima is shifted by up to 2 months.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Hüttl‐Kabus and Böning () also found a more northward position and higher transports between April and August and a more southward position and lower transports between September and March in their model simulation. The seasonal cycle of NEUC transport estimates in TRATL01 is also consistent with the synthesis product of Goes et al (). Similar to Goes et al (), we found a semiannual cycle of the NEUC central position along 23°W, although the timing of maxima and minima is shifted by up to 2 months.…”
Section: Resultssupporting
confidence: 84%
“…This is in agreement with previous observational results (Bourlès et al, , ; Brandt et al, ; Schott et al, , ; Urbano et al, ). The current is weak and likely to be obscured by mesoscale activities (e.g., Goes et al, ; Weisberg & Weingartner, ) and interannual variability (Goes et al, ; Hüttl‐Kabus & Böning, ). Even with this unique data set of 21 ship sections, observations are still too sparse to identify a seasonal variability of the NEUC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations